Chant and Charm: Iconography of Orpheus from Gluck to Moreau - Rodríguez López, María Isabel (Eikón / Imago, 2016)
In this work we suggest an approach to the iconographic evolution of the Thracian magic singer through the European art of the eighteenth and nineteenth centuries, searching the echo of the Classic world in the images, as well as new iconic perspectives and the explicit relation of European artists with the treatment of the myth that was given by Rainiero de Calzabigi in the libretto he wrote to be put in music by Christopher Willibald Gluck (represented for the first time in Viena, 1762). Inspired by the texts of Virgil and Ovid that narrate the hero’s catabasis to rescue his beloved Euridice, the poet from Livorno contributed most notably to the popularity of an issue that became one of the most recurrent Classic themes of the period we have analyzed.